Two new species of Aclodes Hebard, 1928 (Orthoptera: Phalangopsidae: Paragryllinae) from caves in El Peñón, Central-East Andean Colombia - Carvalho, Pedro Henrique Mendes; Ferreira, Rodrigo Lopes (Zootaxa, 2025)
The genus Aclodes (Orthoptera: Grylloidea: Phalangopsidae) currently comprises 36 species. In this study, we describe two new species—Aclodes guane sp. nov. and Aclodes oscari sp. nov.—found in caves in Central-East Andean Colombia, based on distinguished male genitalia characteristics and number of teeth in the stridulatory file of the right tegmina of adult males. Furthermore, we provide comprehensive insights about the conservation status of the caves where the novel species were collected.